Pengaruh Ekstrak Daun Landep (Barleria prionitis L.) Terhadap Glukosa Darah Postprandial dan Histopatologi Pankreas Tikus Yang Diinduksi Aloksan - Sabrina, Salsa; Amin, Muhammad Saiful; Yety Lindawati , Novena (JURNAL FARMASI GALENIKA, 2025)
Indonesia ranks second in diabetes mellitus with 20.4 million sufferers in 2024 and will increase to 28.5 million in 2025. This condition shows the urgency of finding new alternative antidiabetic candidates that can help reduce the number of sufferers. Landep leaves contain flavonoids, saponins, tannins, triterpenoids, and phenolics, which have potential as antidiabetic agents. This study aims to determine the effect of landep leaf extract administration on postprandial blood glucose levels and histopathological improvements in the pancreas in alloxan-induced rats. This experimental study used 25 alloxan-induced rats divided into 5 groups: negative control (CMC-Na 1%), positive control (Metformin 9 mg/200g rat body weight), and landep leaf extract at doses of 100, 200, and 400 mg/kg body weight. Treatment was administered for 14 days. Data analysis was performed using SPSS with ANOVA. The results showed that landep leaf extract at a dose of 400 mg/kg BW had a significant effect on reducing postprandial blood glucose spikes (p=0.634) compared to the positive control metformin, as well as a significant effect on improving the area of the islets of Langerhans (p=0.978) compared to the positive control. Thus, landep leaf extract has an effect on reducing postprandial blood glucose spikes and provides an improvement in the histopathology of the pancreas of alloxan-induced rats.